Information security education: a thematic trend analysis [version 2; peer review: 2 approved] - Manuel Humberto Vásquez Coronado; Aarón Oré León; Ezequiel Martínez Rojas; Ray Harvey Mellin Rubio; Paula Andrea Rodríguez-Correa; Jesus Alberto Jimenez Garcia; Alejandro Valencia-Arias (F1000Research)
The evolution of information technologies has led to a significant increase in information security risks, underscoring the urgent need for professional education in this field to safeguard organizational data. Publications on this topic highlight the necessity of educating individuals about data security, and their number has grown in recent years. This study aims to identify thematic trends in information security education through a bibliometric analysis based on five research questions, following PRISMA guidelines. Ninety-nine documents from Scopus and Web of Science were analyzed, revealing a quadratic growth, with 2023 as the year of greatest research activity. Prominent contributors such as Von Solms, Safa, and Furnell stand out, along with the journal Computers & Security and the significant influence of the United States in this field. The potential is identified in the following areas: information security culture, media, information security regulations, higher education institutions, information security management, and cybersecurity. The study also identifies gaps and proposes a research agenda to address these gaps.